Blast injury prevalence in skeletal remains: Are there differences between Bosnian war samples and documented combat-related deaths?. Issue 6 (November 2017) - Dussault, Marie Christine; Hanson, Ian; Smith, Martin J.
Abstract: Court cases at the International Criminal Tribunal for the Former Yugoslavia (ICTY) have seen questions raised about the recognition and causes of blast-related trauma and the relationship to human rights abuses or combat. During trials, defence teams argued that trauma was combat related and prosecutors argued that trauma was related to executions. We compared a sample of 81 cases (males between 18 and 75) from a Bosnian mass grave investigation linked to the Kravica warehouse killings to published combat-related blast injury data from World War One, Vietnam, Northern Ireland, the first Gulf War, Operation Iraqi Freedom and Afghanistan. We also compared blast fracture injuries from Bosnia to blast fracture injuries sustained in bombings of buildings in two non-combat 'civilian' examples; the Oklahoma City and Birmingham pub bombings. A Chi-squared statistic with a Holm-Bonferroni correction assessed differences between prevalence of blast-related fractures in various body regions, where data were comparable. We found statistically significant differences between the Bosnian and combat contexts. We noted differences in the prevalence of head, torso, vertebral area, and limbs trauma, with a general trend for higher levels of more widespread trauma in the Bosnian sample. We noted that the pattern of trauma in the Bosnian cases resembled the pattern from the bombing in buildings civilian contexts. Variation in trauma patterns can be attributed to the influence of protective armour; the context of the environment; and the type of munition and its injuring mechanism. Blast fracture injuries sustained in the Bosnian sample showed patterns consistent with a lack of body armour, blast effects on people standing in enclosed buildings and the use of explosive munitions. Highlights: We compare patterns of blast injury in mass grave cases to those in combat and civilian contexts. We noted significant differences in patterns of blast injury in the mass grave cases and combat contexts. We also noted similarities in patterns of blast injury in the mass grave cases and civilian contexts. We highlight benefits of a multidisciplinary approach to utilise knowledge of injury patterns in multiple contexts.